Kebijaksanaan Pelayanan Tubektomi dan Vasektomi Sukarela Aspek Pelaksanaan - R. Soeprono, R. Soeprono (Universitas Gadjah Mada, 1983)
Implemenlation aspect of sterilization policyFormulation and implementation of a program providing service on voluntary tubectomy and vasectomy in Indonesia need to be based on clearly defined goals to be pursued and on dynamic ways and means to be utilized.It should be unequivocally understood, that the successful outcome of such a program in support of the national population program, with the end in view of creating a more prosperous community both spiritually and materially, will solely depend on the farsighted vision and determination of the community itself to shape its own future.Key Words: tubectomy – vasectomy - population policy - laparoscopy - sterilization